Геологийн сургалтанд хээрийн дадлагын ач холбогдол, үүрэг - Д.Чулуун; О.Мөнхцэцэг; Д.Хишигсүрэн; Г.Баярмаа (Geological Issues, 2023)
The field training courses are of vital importance in majoring in Geology. During the undergraduate study, students participate in three field trips, the physical geology, the geological mapping and the pre-graduation long term practices. Here, we will the introduce the geological mapping field training. Over last sixty years, the geological mapping field training is being held in various districts such as Urmugtei, Tsenkher River (Khuduu aral), Mushgia khudag, Shine Jinst, and Khugnu-Tarnai, in a period of 4 to 6 weeks. During the field trip, students practice in geological mapping and familiarize with structures. Areas with natural beautiful scenery, understandable geological structure, wide range of sedimentary, igneous and metaphoric rock clear boundary and natural or historical monuments are the most ideal to run the field training. Recently, we conduct die field training in the Khugnu-Tarnai national monument. In Khugnu-Tarnai, lower Paleozoic greenschist facies metamorphic rocks, Lower Carboniferous sedimentary rocks which were intruded by early Mesozoic Khugnukhan complex leicogranite and Cenozoic unconsolidated sediments are the target to map.